0
$\begingroup$

Here is the question:

The PDF of $X_{1},X_{2}...X_{n}$ are $f_X(x)=1-e^{-x},x>0$. They are independent.

Let $M_{n}=max(X_{1},X_{2}...X_{n})$ and $G(z)=\lim_{n\to\infty}[P(\frac{M_{n}-b_{n}}{a_{n}})\leq z]$ and $a_{n}=1,b_{n}=n$. So what is G(z)?


My solution is:

First compute the CDF of $X$, $F_{X}(x)=\int_{0}^{x}f_{X}(t)dt=\int_{0}^{x}(1-e^{-t})dt=x+e^{-x}-1$

Then $F_{M_{n}}(x)=P(M_{n}\leq x)=P(X_{1}\leq x)P(X_{2}\leq x)...P(X_{n}\leq x)=F_{X}(x)^{n}=(x+e^{-x}-1)^{n}$

Finally $G(z)=\lim_{n\to\infty}[P(\frac{M_{n}-b_{n}}{a_{n}})\leq z]=\lim_{n\to\infty}[P(M_{n}\leq a_{n}z+b_{n})]=\lim_{n\to\infty}[P(M_{n}\leq z+n)]=\lim_{n\to\infty}F_{M_{n}}(z+n)=\lim_{n\to\infty}(z+n+e^{-(z+n)}-1)^{n}$

But how to compute that limit? Or did I make mistakes in the computation before? Could anyone help me? Thanks!!!!

$\endgroup$
  • 1
    $\begingroup$ Probably you've mistaken X's CDF for its PDF. For $F(x)$ to be a CDF, at least it should satisfy $\lim_{x \rightarrow +\infty} F(x)= 1$ and for $f(x)$ to be a PDF, we should have $\int_{R}f(x)dx = 1$ $\endgroup$ – Petite Etincelle Nov 17 '13 at 12:15
  • $\begingroup$ Maybe the original question has a mistake, in which the PDF is $1-e^{-x},x>0$. Thanks for your help. $\endgroup$ – TonyLic Nov 17 '13 at 17:30
  • $\begingroup$ But if like you said that $1-e^{-x},x>0$ is the CDF, how to compute the $\lim_{x\to\infty}(1-e^{-(z+n)})^{n}$? $\endgroup$ – TonyLic Nov 17 '13 at 17:39
  • $\begingroup$ we know that $\lim_{n \rightarrow +\infty}(1-\frac{x}{n})^n = \frac{1}{e^x}$, so $\lim_{n \rightarrow +\infty}(1 - \frac{e^{-z}}{e^n})^{e^n} = \frac{1}{e^{e^{-z}}}$, so your limit is equal to $\lim_{n \rightarrow +\infty}(\frac{1}{e^{e^{-z}}})^{\frac{n}{e^n}} = 1$ $\endgroup$ – Petite Etincelle Nov 17 '13 at 18:04
1
$\begingroup$

Since your variables are exponentially distributed, G(z) will be the Gumbel Distribution. The link is for the Fisher-Tippet theorem, which shows how the Gumbel distribution is related to the Fisher-Tippet theorem. The $a_n$ and $b_n$ are special normalizing sequences that are specific to different distributions.

Also, this step in your derivation looks suspect:

$\lim_{n\to\infty}[P(M_{n}\leq a_{n}z+b_{n})]=\lim_{n\to\infty}[P(M_{n}\leq z+n)]=\lim_{n\to\infty}F_{M_{n}}(z+n)$

What made you conclude that the coefficients are 1 and $n$?

This paper may also be very helpful, as it shows how the exponential leads to the gumbel. You will note that $a_n\neq1$ and $b_n\neq n$

$\endgroup$
  • $\begingroup$ Those coefficients are given by the question. Thanks for your help. $\endgroup$ – TonyLic Nov 17 '13 at 17:27
  • $\begingroup$ But in that paper, how could I conclude that $a_{n}\neq $ and $b_{n}\neq n$??? $\endgroup$ – TonyLic Nov 17 '13 at 17:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.